The Social Transformation in Sūrah An-Nisāʾ: A Thematic Qur’anic Study on Challenging Oppressive Practices Against Vulnerable Groups - Mas Zahrotul Firdaus; Mohammad Mas’ud Ubaidillah; Mas Muhammad Haikal Hibatullah (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2026)
The phenomenon of injustice in social structures, gender bias, and oppression of underprivileged populations occurs continuously. Interpretative studies of Surah An-Nisā’ generally focus on legal and normative aspects, while its social and transformative dimensions in rejecting the oppression of the weak have yet to be fully investigated. Surah An-Nisā’ verses 2, 3, 11, 34, and 59 are the focus of the study since these verses contain principles of social justice and protection for vulnerable groups that are often overlooked and misunderstood in social practice. The purpose of this research is to reveal how the Qur'an, through the investigated verses, dismantles the patriarchal and authoritarian social structure. This research emphasizes the values of equality and protection for women, orphans, and the underprivileged. The type of this research is qualitative through literature study and thematic analysis methods as well as contextual hermeneutics, combining the study of asbābun nuzūl, classical exegesis, and contemporary interpretation. The research findings reveal that the Qur'an, through the five verses studied, presents a principle of justice that is transformative, rejects oppression, and upholds the balance of social relations. In conclusion, Surah An-Nisā’ is not to be reduced to a legitimization of power domination, but should be read as a text that upholds equality and social justice relevant across ages. Academically, this research provides a new contribution by expanding the thematic interpretation approach with an interdisciplinary analysis that combines historical, social, and exegesis perspectives, and offers a practical foundation for the development of Quranic exegesis discourse that is responsive to humanitarian and gender equality issues in the modern era.